Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi - Savira, Anggey; Indri Rahmadini; Trisya Oktaviani Indah (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This study aims to analyze the factors that influence economic growth. Economic growth is an important indicator used to measure the success of a country's development because it reflects the increasing capacity of an economy to produce goods and services. This research uses a descriptive approach by examining several factors affecting economic growth, including investment, labor, unemployment, and international trade. The results show that investment plays a significant role in increasing production capacity and encouraging the development of industry and infrastructure. Labor also contributes to economic productivity through the production of goods and services. On the other hand, a high unemployment rate can hinder economic growth because part of the labor force is not absorbed into productive activities. In addition, international trade through export and import activities can support economic growth by expanding markets for domestic products and fulfilling the need for raw materials and technology in the production process. Therefore, economic development policies need to consider these factors to achieve sustainable economic growth and improve public welfare